2010
DOI: 10.1111/j.1399-3046.2010.01431.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced‐intensity conditioning for alternative donor hematopoietic stem cell transplantation in patients with dyskeratosis congenita

Abstract: DC is an inherited bone marrow failure syndrome mainly characterized by nail dystrophy, abnormal skin pigmentation, and oral leukoplakia. Bone marrow failure is the most common cause of death in patients with DC. Because previous results of HSCT with a myeloablative regimen were disappointing, we used a reduced-intensity conditioning regimen for two patients with classic DC, and one patient with cryptic DC who harbored the TERT mutation. Graft sources included two mismatched-related bone marrow (BM) donors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 33 publications
2
31
0
4
Order By: Relevance
“…Therefore a procedure with reduced immunosuppression is currently proposed for patients with dyskeratosis congenita [29][30][31]. Some reports suggest that mycophenolate mofetil and azathioprine may be safely removed from the drug regimen following lung transplantation [28,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore a procedure with reduced immunosuppression is currently proposed for patients with dyskeratosis congenita [29][30][31]. Some reports suggest that mycophenolate mofetil and azathioprine may be safely removed from the drug regimen following lung transplantation [28,32].…”
Section: Discussionmentioning
confidence: 99%
“…None of the treatment was associated with any objective pulmonary improvement assessed either by CT scan or an increase in VC or DLCO by 10% of the predicted value or greater. At the last visit before transplantation, VC and DLCO were 42% [75-22] and 22% [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] of predicted, respectively.…”
Section: Clinical Characteristics At the Diagnosis Of Pulmonary Fibrosismentioning
confidence: 99%
“…Mismatch related or unrelated donors are still associated with a worse prognosis than HSCT from a sibling donor [62]. Fludarabine-containing non-myeloablative conditioning regimens are now increasingly used and might give better short-term results [63][64][65][66]. The literature is scarce on the subjects to draw strong statements.…”
Section: Dyskeratosis Congenita (Dc)mentioning
confidence: 99%
“…Fludarabine-containing non-myeloablative conditioning regimens are now increasingly used and might give better short-term results [64][65][66]70]. The overall data suggest long-term surveillance is important particularly for cancers and pulmonary complications both of which are likely to be secondary to the genetic defect that is not corrected by HSCT.…”
Section: Dyskeratosis Congenita (Dc)mentioning
confidence: 99%
“…2 Several reports have shown that despite being a bone marrow failure syndrome, the use of reduced intensity conditioning preparative regimens are safer, carries less morbidity and has no increased risk of graft failure or rejection. 1,8,[9][10][11][12][13] In some of these reports, however, the ex vivo T-cell depletion was with ATG and in general, the source of stem cells was nonumbilical cord blood stem cells. In both patients in this report, ATG was replaced with alemtuzumab, which has more in-depth lymphocyte depletion with the hope that this will decrease any chance for rejection.…”
Section: Patientmentioning
confidence: 99%